2020
DOI: 10.4081/ija.2020.1510
|View full text |Cite
|
Sign up to set email alerts
|

The overseeding of two cool-season legumes (Hedysarum coronarium L. and Trifolium incarnatum L.) on switchgrass (Panicum virgatum L.) mature stands increased biomass productivity

Abstract: In the Mediterranean rainfed systems, perennial warm-season grasses are profitable crops for the production of herbage as forage or feedstock for bioenergy purposes. During summer, when the production of cool-season crops is scarce, warm-season grasses can improve the productivity and stability of forage cropping systems. In Italy, switchgrass (Panicum virgatum L.) can be cultivated for herbage production or as energy crop. The objective of this work was evaluating if relay intercropping with cool-season legum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…White et al (2018) reported several options to optimize cool-season forage gains and subsequent early spring positive effects on forage production by overseeding bermudagrass [Cynodon dactylon (L.) Pers.]. Overseeding cool-season legumes on switchgrass (Panicum virgatum L.), also increased total biomass productivity (Mantino et al, 2020). Studies evaluating the effect of overseeding on warm-season legumes, such as rhizoma peanut, have not been widely reported in the literature.…”
Section: Ta B L E a Useful Conversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…White et al (2018) reported several options to optimize cool-season forage gains and subsequent early spring positive effects on forage production by overseeding bermudagrass [Cynodon dactylon (L.) Pers.]. Overseeding cool-season legumes on switchgrass (Panicum virgatum L.), also increased total biomass productivity (Mantino et al, 2020). Studies evaluating the effect of overseeding on warm-season legumes, such as rhizoma peanut, have not been widely reported in the literature.…”
Section: Ta B L E a Useful Conversionsmentioning
confidence: 99%
“…Cool‐season annual legumes and grasses are commonly overseeded on warm‐season grass pastures, however results may vary from site to site (Han, Alison, Pitman, & McCormick, 2012; Mantino, Giannini, Tozzini, Bonari, & Ragaglini, 2020; White, Muir, & Lambert, 2018). Overseeding cool‐season forages can potentially increase animal performance during the cool season while optimizing land utilization and improving production throughout the year (Dubeux et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…is one of the most appreciated and employed as forage and pasture crops due to its high productivity and high nutritional value as livestock feed [44]. Also, sulla (Hedysarum coronarium L.), a typical biennial legume widely grown in Central and Southern Italy, could be particularly beneficial for: (i) its capability to exploit clay and alkali soils under rainfed conditions and (ii) its high nutritive value as pasture and hay, mostly due to its high protein content [45]. Among trees, in Italy poplars (Populus spp.)…”
Section: Introductionmentioning
confidence: 99%